A Three-period Samuelson-Diamond Growth - Niels Blomgren-Hansen (Copenhagen Business School (CBS), Department of Economics, 2005)
Samuelson (1958) analyses a three-period model, whereas Diamod (1965) considers a two-period model. This difference poses the question whether the insights derived by analysing the simple two-period model carry over in the more complicated three-period case. They do. The Samuelson model (no productive capital) has only one positive solution (r = n); however, this root is unstable. The Diamond model (no nonproductive abode of purchasing power) has also only one positive solution; the root is stable but inefficient. In a model with both productive capital and a non-productive abode of purchasing power, the inefficient Diamond solution becomes unstable and the socially optimal solution becomes stable.
hdl:10398/7575
Keywords: H00; 330